FORMULASI DAN UJI KESTABILAN FISIK BISKUIT DARI TEPUNG KULIT BUAH LABU KUNING (Cucurbita moschata) - Besse Yuliana; Jelisa Ruru kambuno (Akademi Farmasi Yamasi Makassar, 2026)
Pumpkin peel (Cucurbita moschata) contains various beneficial compounds, including carotenoids (α-carotene, β-carotene, and xanthin), pectin, vitamins A and C, and minerals. The utilization of pumpkin peel as a functional food ingredient can be achieved by processing it into biscuit products. This study aimed to determine whether pumpkin peel flour (Cucurbita moschata) can be formulated into physically stable biscuits and to identify the concentration that produces the best characteristics. This study was an experimental study using four biscuit formulations, namely F1 (20%), F2 (24%), F3 (30%), and F4 (34%) pumpkin peel flour. Evaluations included organoleptic testing, fat content, ash content, moisture content, and carbohydrate content. Organoleptic data were analyzed using the Kruskal–Wallis test, while physicochemical data were analyzed using One-Way ANOVA followed by Duncan's multiple range test.The results of the Kruskal–Wallis test showed that different concentrations of pumpkin peel flour had no significant effect on organoleptic parameters, including color (p=0.407), aroma (p=0.348), taste (p=0.848), and texture (p=0.357). Physicochemical analysis indicated that fat content (p=0.122), ash content (p=0.913), and moisture content (p=0.542) did not differ significantly among the formulations. In contrast, carbohydrate content showed a significant difference (p=0.018), and Duncan's test revealed that F1 differed significantly from F3 and F4. Furthermore, organoleptic evaluation showed that F1 obtained the highest mean preference scores for color (3.63), aroma (3.57), taste (3.37), and texture (3.67).In conclusion, pumpkin peel flour (Cucurbita moschata) can be formulated into biscuits with stable physicochemical characteristics. Formula F1 containing 20% pumpkin peel flour was identified as the best formulation because it achieved the highest panelist preference scores for color, aroma, taste, and texture. Keywords: biscuits, pumpkin peel, Cucurbita moschata, physicochemical properties, organoleptic evaluation.